2008
DOI: 10.1088/0953-8984/20/15/155205
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the structural, optical and electrical transport properties of n-doped CdSe thin films

Abstract: Thin films of (CdSe) 90 (In 2 O 3 ) 10 , (CdSe) 90 (SnO 2 ) 10 and (CdSe) 90 (ZnO) 10 have been grown on glass substrates by the electron beam evaporation technique. It has been found that undoped and Sn or In doped CdSe films have two direct transitions corresponding to the energy gaps E g and E g + due to spin-orbit splitting of the valence band. The electrical resistivity for n-doped CdSe thin films as a function of light exposure time has been studied. The influence of doping on the structural, optical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The crystallite size of nc-CdSe:Zn 1% and nc-CdSe:Zn 5% thin films is calculated by using the Scherrer's formula [31]:…”
Section: Methodsmentioning
confidence: 99%
“…The crystallite size of nc-CdSe:Zn 1% and nc-CdSe:Zn 5% thin films is calculated by using the Scherrer's formula [31]:…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the XRD spectrum indicates that for CdSe:Cu 1% and CdSe:Cu 5% thin films, the films grow according to the preferential orientation of the hexagonal phase. In fact, an estimate of the grain size D according to the DebyeScherrer [28] relationship gives the average grain size D = 31 and 44 nm for CdSe:Cu (1%) and CdSe:Cu (5%), respectively. Thus, the increase of the Cu content results in increase of the grain size of the films.…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency and fill factor of these PEC solar cells were increased from 0.79% and 0.46 to 2.12% and 0.49, respectively, with indium doping in CdS 0.2 Se 0.8 thin films. Thin films of (CdSe) 90 (In 2 O 3 ) 10 , (CdSe) 90 (SnO 2 ) 10 and (CdSe) 90 (ZnO) 10 have been grown on glass substrates by H. M. Ali et al [124] using electron beam evaporation technique. It was been found that undoped and Sn or In doped CdSe films had two direct transitions corresponding to the energy gaps E g and E g +∆ attributed to spin-orbit splitting of the valence band.…”
Section: Materials Properties Of Cdse:in Solid Solutionsmentioning
confidence: 99%